Vanadium MXene-Modified Disposable Screen-Printed Electrodes for Highly Sensitive Glucose Sensing - Akanksha Shrivastav; Sonam Singh; Reema Rawat; Annu Mishra; Pankaj Kumar; Ajeet Kaushik; Ashish Mathur (ECS Sensors Plus)
Diabetes mellitus is a prevalent metabolic disorder that needs precise and real-time measurement of glucose for disease management. Traditional glucose sensing techniques, despite their widespread use, are plagued by problems like biofouling, limited working lifetimes, and low sensitivity in hypo- and hyperglycaemia ranges. To overcome these problems, this work presents the development of a novel enzyme-based electrochemical biosensor based on two-dimensional (2D) Vanadium MXene (V _2 CT _x ) for enzymatic glucose sensing. Enzyme-based electrochemical sensors are more accurate and specific than traditional glucose sensing methods. The addition of Vanadium carbide MXene enhances interlayer distance, providing enhanced stability, biocompatibility, and signal amplification. X-Ray Diffraction (XRD), Fourier Transform Infra-Red spectroscopy (FTIR), Field Emission-Scanning Electron Microscopy (FE-SEM), Raman spectroscopy, BET and X-ray photoelectron spectroscopy (XPS), and Transmission electron microscopy (TEM) were used to characterize the synthesised MXene. Cyclic Voltammetry (CV) and Electrical Impedance Spectroscopy (EIS) have been employed to assess the effectiveness of the glucose monitoring device and confirm the successful immobilization of Glucose Oxidase (GOx). With a limit of detection (LoD) of 0.294 nM and limit of quantification (LoQ) of 0.893 nM for hypoglycaemic concentration and a LoD of 0.0017 mM and LoQ of 0.005 mM for hyperglycaemic concentration, it suggests that the developed biosensor is highly sensitive. The modified electrode offers a shelf life of over a month and robust stability for potential applications in point-of-care settings. The results have significance not just for the continuous advancement of glucose monitoring technology but also for better medical diagnosis and diabetic treatment.